STRATEGI INTERNET MARKETING PADA BISNIS KULINER DI KOMUNITAS WISATA TASIKMALAYA - Abdullah, Yusuf; Rosliyati, Ati; Nugraha, Aa Willy (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- The research objective was to determine the internet marketing strategy through social media in a typical culinary business in Tasikmalaya City. Design/methodology/approach- Descriptive-qualitative research methods were used to describe internet marketing strategies that were applied through analysis of market segmentation, target markets, and positioning and its implication of social media optimization (SMO). Observation, deep interview and literature study techniques were carried out in obtaining the data. The culinary business that was studied was the typical culinary of Tasikmalaya, namely Tutug Oncom (Tutug Oncom Instant Titasix). Findings- The results showed that culinary business in the Tasikmalaya Culinary Community (KWKT) had implemented internet marketing, especially implementing social media optimization in supporting internet marketing activities with social media. Implications- Through internet marketing, it was expected that typical culinary businesses in Tasikmalaya could optimize technological advancements through social media such as Facebook, Instagram, and other social media in marketing culinary products. Keywords: Internet marketing; Segmenting; Targeting; Positioning; Social Media Optimization